KARAKTERISTIK FISIKOKIMIA DAN PENERIMAAN KONSUMEN TERHADAP BAKSO SURIMI IKAN LELE SANGKURIANG (Clarias gariepinus var. sangkuriang) - Febiwina, Febiwina; Diachanty, Seftylia; Irawan, Irman; Pamungkas, Bagus Fajar; Zuraida, Ita (Media Teknologi Hasil Perikanan, 2024)
Fishball are processed fishery products that use mashed meat or surimi and mixed with tapioca flour as a thickener to improve the texture of the meatballs. This study aims to determine the physicochemical characteristics of catfish surimi fishtballs with the addition of tapioca flour and the best concentration of flour to produce meatballs that are liked by consumers. This research used surimi treatment of sangkuriang catfish and tapioca flour consisting of 100g surimi without tapioca flour (P0), 95g surimi : 5g tapioca flour (P1), 90g surimi : 10g tapioca flour (P2), 85g surimi : 15g tapioca flour (P3) and 80g surimi : 20g tapioca flour (P4). This research method used a completely randomized design (CRD) with chemical observations (moisture, ash, protein and fat content) physical (expressible moinsture content, color and folding test) and Kruskal-wallis observations for hedonic tests (taste, aroma, color and texture). The results showed that the ratio of catfish surimi and tapioca flour had a significant effect (p<0.05) on moisture content, ash content, protein, fat and expressible moinsture content, but did not have a significant effect (p>0.05) on the results of folding test and color of fishball. The addition of tapioca flour has a significant effect on the hedonic test on the parameters of taste, aroma, color and texture. 95g surimi : 5g tapioca flour (P1) is the best treatment with the average quality value on the parameters of taste, aroma, color, and texture is 7 (like).